The Impact of Multimedia-Based Education on Dietary Diversity and Protein Intake among School Children: A Quasi-Experimental Analysis - Fadyassyifa Nurhafidza; Widya Rahmawati; Fuadiyah Nila Kurniasari (Journal of Health and Nutrition Research, 2026)
Nutritional problems among school-age children in Indonesia remain a concern due to low consumption of balanced diets. Basic Health Research 2018 reported that only 5.3% of children meet the recommended fruit and vegetable intake. This highlights the need for more effective nutrition education strategies, with multimedia-based approaches offering a more engaging and understandable way to promote healthy eating behaviors. This study aimed to assess the effectiveness of multimedia-based balanced nutrition education in improving the eating behavior of school-age children. A quasi-experimental study with a one-group pre-test–post-test design was conducted among 75 students in grades IV and V at SDN Seuriget, Langsa City, selected using total sampling. The intervention was implemented over five weeks through a gradual educational approach combining leaflets and animated videos on balanced nutrition. Data were collected at four time points: before the intervention (pre-test), after leaflet education (post-test 1), after animated video education (post-test 2), and one week after the intervention (follow-up). Eating behavior was assessed using the IDDS and dietary intake measurements. The results showed significant improvements in several variables. The median IDDS increased from 6 to 11 (p < 0.001). Median protein intake increased from 49.9 g to 57.4 g (p < 0.001). Median fat intake decreased significantly from 72.7 g to 54.8 g (p < 0.001), while carbohydrate intake showed significant changes (p < 0.001). However, energy intake did not show a statistically significant change (p = 0.667). In conclusion, multimedia based nutrition education improved dietary diversity and protein intake. These result suggest that external factors such as family dietary habits and household food availability may affect children’s overall nutrient intake.